ANALISIS PENUTUPAN LAHAN DAN PERUBAHANNYA MENJADI KELAPA SAWIT DI INDONESIA (Studi Kasus di 5 Pulau Besar di Indonesia periode 1990 s.d 2010) - Petrus Gunarso; Manjela Eko Hartoyo; Yuli Nugroho (Jurnal Green Growth dan Manajemen Lingkungan, 2013)
Indonesia is one of the largest crude palm oil (CPO) producing countries in the world and at the same time have experienced high levels of deforestation. The link between deforestation and expansion of oil palm plantation has been a source of controversy, which has been exacerbated by the lack of objective quantitative information on the nature of land use and land cover change and the expansion of oil palm plantations. This report provides an independent analysis of land use and land cover change for a broad range of land cover classes for five main Islands in Indonesia, namely Sumatra, Java, Kalimantan, Sulawesi, and Papua based on Landsat TM satellite images. Visual analysis and on screen digitizing methods were employed to create a nation-wide land cover classification that spans two decades (1990 to 2010). Three temporal epochs (1990 to 2000, 2000 to 2005 and 2005 to 2010) correspond to a period of time with significant changes in land cover and land uses in Indonesia. Expansion of oil palm plantation in Indonesia shows that most of the expansion exists as a follow on transition from disturbed forest (secondary forest), agricultural lands (mainly rubber plantation), and low biomass land cover types, including shrub land and grassland than formerly reported to be majority from undisturbed forest (primary forest).